Evaluation of Rational Drug Use based on Indicators of Diseases and Facilities at Community Health Centers in Districts in Semarang - Nisa Febrinasari; Abdur Rosyid; Leny Angelina (Borneo Journal of Pharmacy, 2019)
Rational drug use (RDU) is an indicator to evaluates a treatment given to patients, like proper medication, precise diagnosis, precise dosing. Community Health Center (CHC) has the risk of irrational drug use. In this study, researchers selected N and BL CHC, aiming to evaluate the prescribing indicators based on three diseases which are non-pneumonia acute respiratory infection (ARI), non-specific diarrhea and myalgia, and the facility indicators with DOEN (list of essential national medicines) availability and 20 mandatory drugs. This research was a descriptive-analytical study with cross-sectional methods where the data retrieval of the prescribing is taken from January to December 2018. The study used the normality test and homogeneity test before independent sample T-test, from the third outcome of the test, the N and BL CHC could be said to differ significantly of RDU. It can be concluded that rational drug use is reviewed from a prescribing indicator based on disease and facility indicator. The results of RDU are rational in N CHC, in contrast with BL CHC which is not rational with the results of the RDU in N CHC is 101.44% and BL CHC is 89.81%. The results of N CHC is better than BL CHC, which both CHCs have fulfilled the target of the government, for 68% in 2018. In both CHCs for the facility indicator, there are a DOEN and 20 essential medicines.